2001
DOI: 10.1002/jnr.1243
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term evolution of autoreactive T cell repertoire in multiple sclerosis

Abstract: T cells reactive to self-antigens are present in the peripheral blood of patients with autoimmune diseases as well as in healthy subjects. Although T cell-response to the self-myelin antigen myelin basic protein (MBP) has been widely investigated in multiple sclerosis (MS) patients, very little is known about the evolution over time of this response and its correlation with the disease activity. In recent years magnetic resonance imaging (MRI) techniques have provided new tools for following the inflammatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Various B-and T-cell responses to CNS autoantigens have indeed been described in MS patients, but none of the trials reached a verdict on the accusation of their involvement in initiating and perpetuating the disease [15,16]. A number of reports have described more subtle changes in function of the myelinspecific T cells in MS patients [17,18], including interleukin (IL)-2 and costimulation responsiveness, resistance to hypoxanthine-guanine phosphoribosyl-transferase, responses to interleukins and avidity for antigen [16]. Again, none is generally accepted as a CD4 + cell marker of MS, although in the composition of its function there are additional clues to the pathogenesis of MS.…”
Section: T-and B-cell Immune Responses As Biomarkers Of Msmentioning
confidence: 99%
“…Various B-and T-cell responses to CNS autoantigens have indeed been described in MS patients, but none of the trials reached a verdict on the accusation of their involvement in initiating and perpetuating the disease [15,16]. A number of reports have described more subtle changes in function of the myelinspecific T cells in MS patients [17,18], including interleukin (IL)-2 and costimulation responsiveness, resistance to hypoxanthine-guanine phosphoribosyl-transferase, responses to interleukins and avidity for antigen [16]. Again, none is generally accepted as a CD4 + cell marker of MS, although in the composition of its function there are additional clues to the pathogenesis of MS.…”
Section: T-and B-cell Immune Responses As Biomarkers Of Msmentioning
confidence: 99%
“…Moreover, topological architecture is being compared between networks constructed for a priori defined clinical groups with the aim being one of identifying illness-specific network features such as local changes in connectivity and the appearance of hub transcripts or proteins (Fuite, Vernon and Broderick, 2008a). This is a static analysis and there is little if any direct consideration of the subsequent dynamical modes supporting the emergence and exacerbation of symptoms, be they sustained or episodic in illnesses such as multiple sclerosis (Vergelli et al, 2001) and chronic fatigue syndrome (Aschbacher et al, 2012). Even directed graphs that encode this dynamic information are still compared in terms of their structure, for example motif frequency, rather than the dynamics of information flow that they describe (Frankenstein, Alon and Cohen, 2006).…”
Section: Linking Parts Within Scales and Compartments Of Biologymentioning
confidence: 99%
“…As IFN-γ is still the most commonly measured Th1 cytokine (Hellings et al, 2001;Vergelli et al, 2001;Weissert et al, 2002) and has been shown to be involved in MS pathogenesis (Panitch et al, 1987;Woodroofe and Cuzner, 1993), we limited our results presented here to IFN-γ production by myelin-specific T cells. To avoid bias, analysis of the flow cytometrybased assay was performed without the evaluator knowing the patients' clinical status.…”
Section: Flow Cytometry-based Assaymentioning
confidence: 99%